2020
DOI: 10.1016/j.compfluid.2019.104343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grid resolution on the spectral characteristics of noise radiated from turbulent jets: Sound pressure fields and their decomposition

Abstract: Jet noise remains a key target for aircraft noise reduction in the foreseeable future. While being extremely challenging, the requirement of predicting both low and high frequency noise spectra is increasingly important for design purposes. Novel approaches are needed to overcome the current numerical limitations in capturing the required broad noise spectra. Once su ciently resolved, the energy contents of the numerically simulated near-and far-field sound pressure have intrinsic correlations among di↵erent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…To illustrate the effect of grid refinement on high-frequency noise predictions, results from the LES/FWH study of Angelino et al [53] are shown for a round nozzle at M j = 0.9 and Re j = 10 6 in Fig. 27.…”
Section: Figure 26 Coupled Les (Inner) Jet Domain and Lee (Outer) Acoustic Propagation Domain From Ref 49mentioning
confidence: 99%
See 3 more Smart Citations
“…To illustrate the effect of grid refinement on high-frequency noise predictions, results from the LES/FWH study of Angelino et al [53] are shown for a round nozzle at M j = 0.9 and Re j = 10 6 in Fig. 27.…”
Section: Figure 26 Coupled Les (Inner) Jet Domain and Lee (Outer) Acoustic Propagation Domain From Ref 49mentioning
confidence: 99%
“…Naqavi et al [38] opted for a combined RANS-LES approach where the RANS equations are solved internal to and surrounding the nozzle wall and gradually blended into an LES region where 48m cells were used. Angelino et al [53] retained LES for both the internal nozzle (wall stress model) and jet flow and carried out a grid resolution study (with 5-80m cells) to explore the effect of finer meshes on flow/noise predictions. Both FWH treatments chose similarly located noise source containing surfaces and applied averaging or filtering over multiple 'end plates' to remove pseudo-sound generated by vortical structures crossing the FWH surface.…”
Section: Civil Aerospace Applications 31 Cold and Hot Single Jet In Stagnant Surroundingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao Weiguo et al 15 analyzed the transient characteristics of a centrifugal pump while pumping a sandy two-phase flow. Reviewing the literature indicates that many scholars have used CFD, sound analogy theory, and experimental methods to study the fluid-structure coupled noise of aircraft wings and nozzles 1618 as well as the coupled noise of ship rudder bodies and fluids. 1921 Results of these investigations are helpful to explore the acoustic characteristics of fluid–structure coupling.…”
Section: Introductionmentioning
confidence: 99%